Governance for the Sustainable Development Goals : Exploring an Integrative Framework of Theories, Tools, and Competencies - Monkelbaan, Joachim (Singapore, Springer, 2019)
This book provides a detailed overview of governance for the Sustainable Development Goals (SDGs). The purpose of the unique integrative approach in this book is to address the fragmentation of governance that is a critical barrier to achieving the SDGs. The main question addressed is: What are the crucial elements and the organizing logic of an integrative framework that is suitable for analysing governance for the SDGs and for implementing the transitions that we need towards a more sustainable world? This transdisciplinary book first proposes a combination of innovative governance theories that can improve the analysis and practice of sustainability governance. Secondly, it explores the interests of core actors in a number of case examples. And thirdly, it offers recommendations for improving the study and practice of sustainability governance. The findings presented form the basis for a new approach to governance towards objectives such as the SDGs: Integrative Sustainability Governance (ISG). The ensuing ISG framework includes indicator frames within the pillars of power, knowledge and norms. The book concludes that the transformation of crisis into sustainability transitions requires a deeper consideration of risk management that strengthens resilience; systems deliberation that complements democracy; and behavioral insights that elevate human awareness and collaboration. Whether you are a student, expert, or practitioner with an interest in the SDGs, this handbook will surely be a comprehensive and useful companion.
Chapter 1. Introduction: Objectives, Substantive Issues, and Structure of this Book -- Chapter 2. Overview of Governance Theories that are relevant for the SDGs -- Chapter 3. Laying out Actors and Dynamics in the 2030 Agenda for Sustainable Development -- Chapter 4. Exploring Some Specific Case Studies -- Chapter 5. Governance Pillars and Competences: Power, Knowledge, and Norms as Cross-cutting Issues in Governance for the SDGS -- Chapter 6. Inferences on Improving Integrative Sustainability Governance -- Chapter 7. Conclusions: The Integrative Sustainability Governance Framework and ways Forward.
Keywords: Economic development; Environmental management; Industrial management -- Environmental aspects; Sociology, Urban; Sustainable development; Sustainable Development; Development Studies; Environmental Management; Sustainability Management; Urban Studies/Sociology.